Application of Response Surface Methodology (RSM) to Study Transesterification of Palm Oil in the Presence of Zeolite-A as Catalyst - Kamisah Delilawati Pandiangan; Khoirin Nisa; Wasinton Simanjuntak; Diska Indah Alista; Erika Noviana; Selvia Anggraini Hasan (Journal of Multidisciplinary Applied Natural Science, 2024)
In this research, the application of response surface methodology with central composite design (RSM-CCD) to optimizetransesterification of palm oil in the presence of zeolite-A as catalyst was investigated. Zeolite-A was synthesized from rice husk silica (RHS) and food-grade aluminium foil using hydrothermal method and then characterized using XRD and SEM. The synthesized zeolite was then applied to an optimized transesterification reaction using response RSM with three factorial levels, for three variables including methanol to oil ratio, catalyst load, and reaction time. The experimental results indicate that the yield of 99% was achieved at optimum conditions of methanol to oil volume ratio of 6, catalyst load of 9.6%, and reaction time of 4.3 hours. The results of experiments and predicted results based on the RSM model are in agreement as shown by the p-value less than 0.05 at a confidence level of 95%.